2013
DOI: 10.1530/eje-13-0286
|View full text |Cite
|
Sign up to set email alerts
|

Association of risk variants for type 2 diabetes and hyperglycemia with gestational diabetes

Abstract: Our study suggests that GDM and T2D share a similar genetic background. Our findings also provide further evidence that risk variants of MTNR1B are associated with GDM by increasing fasting plasma glucose and decreasing insulin secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
2
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 38 publications
8
86
2
9
Order By: Relevance
“…The BMI, age, and HbA1c parameters of pregnant women in the groups in question were similar to those in pregnant women in groups of similar studies (Huopio et al, 2013;Takhshid and Zare, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…The BMI, age, and HbA1c parameters of pregnant women in the groups in question were similar to those in pregnant women in groups of similar studies (Huopio et al, 2013;Takhshid and Zare, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Independent genome-wide association studies in European populations identified single nucleotide polymorphisms near MTNR1B that were associated with fasting plasma glucose, reduced beta cell function, and significantly increased T2DM risk: rs1387153 and rs10830963. 104, 105 Expression of these two single nucleotide polymorphisms is also significantly associated with the development of gestational diabetes, 106, 107 as well as elevated fasting glucose and reduced insulin secretion after parturition. 106 A diagnosis of gestational diabetes is one of the highest predictors for the later development of T2DM.…”
Section: The Mt2 Receptor: Targeting Dysregulated Insulin Secretion Amentioning
confidence: 99%
“…Among these, the risk allele (G) of rs10830963 in the melatonin receptor 1B (MTNR1B) gene (MTNR1B) shows the highest OR for GDM in a Finnish study [4].…”
Section: Introductionmentioning
confidence: 99%